2010
DOI: 10.1080/17457289.2010.490707
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐National versus Individual‐Level Differences in Political Information: A Media Systems Perspective

Abstract: A BSTRACT We propose a context-dependent approach to the study of political information. Combining a content analysis of broadcast news with a national survey measuring public awareness of various events, issues, and individuals in the newsAs Walter Lippmann (1922) pointed out in his classic account of public opinion, politics is inherently a mediated experience. Indeed, issues and events not covered by the media fail to enter into the political consciousness. Yet, despite the indispensable role of the news me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
110
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 27 publications
8
110
1
Order By: Relevance
“…Prior research indicates that a saturated news environment can close the knowledge gap between individuals motivated to consume news and those who are not, as citizens are more likely to glean political knowledge if relevant information is widely available (e.g. Elenbaas et al, 2014;Iyengar et al, 2010;Shehata, 2013). Yet the results of the present study suggest that the benefits of such a saturated media environment may not always extend to social media.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research indicates that a saturated news environment can close the knowledge gap between individuals motivated to consume news and those who are not, as citizens are more likely to glean political knowledge if relevant information is widely available (e.g. Elenbaas et al, 2014;Iyengar et al, 2010;Shehata, 2013). Yet the results of the present study suggest that the benefits of such a saturated media environment may not always extend to social media.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies support the passive learning hypothesis, noting that information environments containing high levels of political news and information can enhance political knowledge through mere exposure, even for individuals who do not actively expose themselves to news (e.g. Elenbaas et al, 2014;Iyengar et al, 2010;Kobayashi & Inamasu, 2015;Shehata, 2013;Shehata et al, 2015;Tewksbury et al, 2001). Extending the findings in support of passive learning to the present study, it is possible that individuals high in news-finds-me perceptions may passively learn about politics despite not actively seeking the news through their use of other media.…”
Section: News-finds-me Effect On Political Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Recent research, however, points at substantial differences across media systems. Cross-national comparative research suggests that the presence of popular public service broadcasting institutions increases the "inadvertent" audience for news and, thereby, the opportunities to learn among less politically interested citizen groups despite the abundance of choices Curran, Iyengar, Lund, & Salovaara-Moring, 2009;Esser et al, 2012;Iyengar et al, 2010). Unlike market-driven media systems such as those of the United States, most European broadcast markets are dualistic where strong public service broadcasting coexists with commercial competitors.…”
mentioning
confidence: 95%
“…These voters are the most likely to be undecided until the election campaign begins, and are potentially more open to political news coverage influencing their vote choice-even if they pay cursory attention to it (Albaek et al 2014: 102;Denemark, Ward and Bean 2007: 90-91). Doris Graber (2001), Klaus Schoenbach and Edmund Lauf (2002) and Shanto Iyengar et al (2010) have found that people who are the least politically interested tend to acquire most of their information about current affairs from news media. This is important in the context of Australia's compulsory voting system whereby most adults do vote, regardless of their political interest.…”
Section: Media Effects and Undecided Votersmentioning
confidence: 99%